Auditory and Visual Cues for Topic Maintenance with Persons Who Exhibit Dementia of Alzheimer's Type. (10th June 2015) - Teten, Amy F.; Dagenais, Paul A.; Friehe, Mary J.
Abstract : This study compared the effectiveness of auditory and visual redirections in facilitating topic coherence for persons with Dementia of Alzheimer's Type (DAT). Five persons with moderate stage DAT engaged in conversation with the first author. Three topics related to activities of daily living, recreational activities, food, and grooming, were broached. Each topic was presented three times to each participant: once as a baseline condition, once with auditory redirection to topic, and once with visual redirection to topic. Transcripts of the interactions were scored for overall coherence. Condition was a significant factor in that the DAT participants exhibited better topic maintenance under visual and auditory conditions as opposed to baseline. In general, the performance of the participants was not affected by the topic, except for significantly higher overall coherence ratings for the visually redirected interactions dealing with the topic of food.